2013
DOI: 10.1109/tmag.2012.2218583
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the 3-D Coil System's Orthogonality

Abstract: Two methods were tested for calibration procedures of the 3-D coil system which is used as a source part of the magnetic tracker. Precise magnetometer's positions with respect to the coil system were used for determining of the nonorthogonality of the coil system as well as for determining of the magnetic moment. The needed number of the reference positions was measured to calculate six unknown calibrated parameters. In comparison, the 3-D coils system was also calibrated with a method which employs the orthog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In the current paper, we followed these basic measurement principles, reproduced in worldwide accepted publications such as [5][6][7]. In agreement with the abovementioned research, it was confirmed that, in any case, the angular compensation of the yaw, pitch, and roll are entirely necessary.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the current paper, we followed these basic measurement principles, reproduced in worldwide accepted publications such as [5][6][7]. In agreement with the abovementioned research, it was confirmed that, in any case, the angular compensation of the yaw, pitch, and roll are entirely necessary.…”
Section: Introductionsupporting
confidence: 66%
“…In agreement with the abovementioned research, it was confirmed that, in any case, the angular compensation of the yaw, pitch, and roll are entirely necessary. Our method of measuring the angular deviations of the sensor coil axis did not use Helmholtz coils, as in [7], but relied on the precise and stable positioning of the sensor in the proximity of the WPT emitter coil.…”
Section: Introductionmentioning
confidence: 99%
“…3). The comparison was done for the horizontally located E-W coils only in order to verify the uncertainty of the coil calibration principle [10]. The two coils, the unknown X (the E-W axis of the Helmholtz coils in our case) and the coil standard E were connected in the two branches with variable resistors R RX and R RE.…”
Section: Calibration Against Magnetic Flux Density (Mfd) Standardmentioning
confidence: 99%
“…The procedure uses a scalar Overhauser magnetometer to calibrate the coil constants and the angular alignment of the triaxial Helmholtz coils -the details are described in [10] together with uncertainty analysis in [11]. The details of the setup are depicted in Fig 2 . The calibration results express the 3 coil sensitivities and their respective angular alignment.…”
Section: B Triaxial Coils Calibrationsmentioning
confidence: 99%